2003
DOI: 10.1002/dev.10155
|View full text |Cite
|
Sign up to set email alerts
|

Can behavioral evolution be measured on a staircase? a commentary

Abstract: The serious, comparative study of behavioral complexity that Greenberg et al. advocate is a progressive direction for the field, but their proposal to separate comparative psychology from its roots in evolutionary biology seems regressive. Modern evolutionary theory has been broadened within biology to include development and paleontology alongside natural selection, making closer integration with that discipline particularly timely. Such an integrated evolutionary approach in psychology would offer a useful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…A recent study also indicated that levels DNA methylation in the GR1 7 promoter methylation do not differ significantly between mixed-sex litters and female-only litters, suggesting that our epigenetic data may be informative for studies of mix-sex litters (Kosten, Huang, & Nielsen, 2014). Some previous studies, however, have reported that mothers preferentially lick male pups (Moore & Morelli, 1979), potentially as a result of a shorter latency in male offspring to extend their legs and thereby facilitate licking (Moore, 2004). It is thus possible that removal of the male offspring in this study affected the dynamics of interactions between dams and offspring.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also indicated that levels DNA methylation in the GR1 7 promoter methylation do not differ significantly between mixed-sex litters and female-only litters, suggesting that our epigenetic data may be informative for studies of mix-sex litters (Kosten, Huang, & Nielsen, 2014). Some previous studies, however, have reported that mothers preferentially lick male pups (Moore & Morelli, 1979), potentially as a result of a shorter latency in male offspring to extend their legs and thereby facilitate licking (Moore, 2004). It is thus possible that removal of the male offspring in this study affected the dynamics of interactions between dams and offspring.…”
Section: Discussionmentioning
confidence: 99%